LITERASI POLITIK MASYARAKAT PESISIR DAN MANAJEMEN PARTAI POLITIK - Asep Abdul Sahid; Kadar Nurjaman (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
This article is the result of a research-based community service aimed to describe, identify and reveal how the management of political parties at the lower level that can ensure the actualization of its functions. Political parties are attached to the functions of political education that can create a political literacy society. That is people who are politically knowledgeable and politically empowered. Communities that can participate actively in any political activities of society, nationality and statehood. However, there are still many political blind people who are easily mobilized or even politically marginalized. This is for example found in coastal communities. That fact is possible because: first, geographically coastal tends to be a periphery; secondly, the optimal functioning of coastal political parties as a means of political education; And third, the lack of activities of coastal political parties that empower the community. Training and management of political party management becomes an action strategy and a choice of method of devotion. The corpus of community service is the management of political parties and coastal community leaders in Cikelet Sub-district, Garut. This community service applies management theories, political literacy and good governance. Based on the theories and methods, this community service indicates that trainees and assistance can improve capacity, capability and sensitivity for guaranteeing synergy of political party functions with the political literacy of coastal communities.